(untitled) (Research, Society and Development, 2021)
Objective: To analyze, from the adolescent’s perspective, the biopsychosocial elements that make up the adolescent and their interface with health. Method: Descriptive study, with a qualitative approach based on the theoretical framework of Symbolic Interactionism. The collection took place through individual interviews, via virtual platform, with 12 adolescents, aged between 13 and 16 years. For data analysis, the discourse analysis was adopted. Results: For adolescents, adolescence is marked by bodily, physiological and behavioral transformations that, to a certain extent, influence their development and health. Self-care, physical activity, sleep patterns and adequate nutrition were considered important for adolescent health. They highlight the increase in responsibilities and, in some circumstances, decision-making related to their future life projects. They consider adolescence as a difficult phase, correlated with difficulties in interpersonal relationships, especially in relation to friendships, low esteem, increased concerns and changes in mood associated with maintaining their psychological well-being. Final Considerations: Understanding the meanings of adolescence and the context in which the adolescent is inserted favors the development of health education practices that enhance the health promotion of this public. It is understood that this phase of life should not be seen as a period of transition, but as part of a process of maturation and intense learning.